2017
DOI: 10.1088/1478-3975/aa6876
|View full text |Cite
|
Sign up to set email alerts
|

A new scenario for gravity detection in plants: the position sensor hypothesis

Abstract: The detection of gravity plays a fundamental role during the growth and evolution of plants. Although progress has been made in our understanding of the molecular, cellular and physical mechanisms involved in the gravity detection, a coherent scenario consistent with all the observations is still lacking. In this special issue article, we discuss recent experiments showing that the response to inclination of shoots is independent of the gravity intensity, meaning that the gravity sensor detects an inclination … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 82 publications
2
56
0
1
Order By: Relevance
“…Overall, our study supports the growing consensus that the sensor of gravity in plants is a position sensor, related to the averaged position of the statoliths inside the cell ( 4 , 20 , 28 ) [the position-sensor hypothesis ( 2 )]. When statocytes are inclined, statolith piles flow to recover a horizontal free surface like a liquid.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Overall, our study supports the growing consensus that the sensor of gravity in plants is a position sensor, related to the averaged position of the statoliths inside the cell ( 4 , 20 , 28 ) [the position-sensor hypothesis ( 2 )]. When statocytes are inclined, statolith piles flow to recover a horizontal free surface like a liquid.…”
Section: Discussionsupporting
confidence: 86%
“…Biological sensors display a wide range of strategies that combine sensitivity and robustness to cope with a fluctuating and noisy environment. In this respect, the gravity sensor of plants is unique ( 1 , 2 ). It is found in specific cells, called statocytes, in which tiny assemblies of starch-rich particles, called statoliths, sediment at the bottom of the cell and give the direction of gravity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that the gravitropic response depends upon the angle between the statoliths free surface and the vertical, but not on the intensity of the gravitational field and the pressure of statoliths against the cell membrane (54). A possible mechanism is that the contact between the statoliths and the cell membrane may trigger relocalization of PIN membrane transporters and a redirection of auxin flux (53). Here, we follow this hypothesis and, accordingly, assume that gravity drives an advective flow of auxin J stim = kAf .…”
Section: Examplesmentioning
confidence: 99%
“…Statocytes contain dense organelles (statoliths) that sediment under the effect of gravity. Tilting of the plant causes statoliths to avalanche and to form a free surface perpendicular to the gravity vector, providing orientational information to the cell (53). It has been observed that the gravitropic response depends upon the angle between the statoliths free surface and the vertical, but not on the intensity of the gravitational field and the pressure of statoliths against the cell membrane (54).…”
Section: Examplesmentioning
confidence: 99%